Estimate the conservation value of ecotourism resources in Taman Negara Sungai Relau, Pahang - Hassin, Nor Hizami; Yacob, Mohd Rusli; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
The purpose of this study is to estimate the conservation value of ecotourism resources among the visitors in Taman Negara Sungai Relau, Pahang. The application of dichotomous choice of Contingent Valuation Method (CVM) is used in measuring the willingness to pay (WTP) from the respondents. A total of 300 respondents were obtained which randomly choose during face to face interviewed. The conservation value of the ecotourism resources in TNSR were estimated by using single-bounded dichotomous choice method. The logit regression model result indicates that BID, INCOME and EDU variables were significance and influences the visitors’ willingness to pay for the entrance permit to TNSR. The estimated mean WTP was RM 8.26 per visit. Meanwhile, the expected benefit or total value of conservation of the ecotourism resources in TNSR was RM 148,085.28. The finding of the study recommends that the park management should engage the visitors into its conservation endeavor as well as share the benefits with them. The study reveals that visitors are willing to pay higher than the current (RM1) entrance fees. Thus, results of this study are important in assists the TNSR management in establishing an efficient and realistic entrance permits to visitors for sustainable of the ecotourism resource in future.